Meninjau Nilai-Nilai Spiritualitas Ekologis dalam Ritus Roko Molas Poco Pada Masyarakat Manggarai - Marselinus Langgor; Felix Riondi Sugar; Stepani Rosmila; Simon Oktavianus Nailiu; Oktavianus Nuba Dua; Antonius M.A. Wangga; Protasius Karsa; Fridolin Mawangsuri Fallo (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
This study aims to examine the values of ecological spirituality in the Roko Molas Poco ritual among the Manggarai people. This tradition is understood not only as a cultural practice in the construction of traditional houses (mbaru gendang), but also as an expression of the harmonious relationship between humans, nature, and the Creator. This study employs a qualitative approach using library research to examine various sources of literature related to ecology, theology, and Manggarai local wisdom. The results indicate that Roko Molas Poco embodies strong ecological spiritual values, reflected in every stage of the ritual from preparation and execution to the carrying of the siri bongkok. These values affirm that nature is viewed as a sacred creation of God that must be preserved, not exploited. This tradition also demonstrates that the relationship between humans and nature is not one of objectification, but rather a subject-to-subject relationship characterized by mutual respect and complementarity. Thus, Roko Molas Poco serves as a form of local ecological spirituality that is relevant in addressing the current environmental crisis.